"Doctor, What Happens After My Meniscectomy?". (6th November 2019) - Smith, John-Rudolph H.; Houck, Darby A.; Kraeutler, Matthew J.; McCarty, Eric C.; Frank, Rachel M.; Vidal, Armando F.
Abstract : It is imperative that surgeons educate their patients on what to expect following a meniscectomy. A high preinjury activity level, younger age, medial meniscectomy, and smaller meniscal resection play a role in reducing the time until patients are able to return to sport. Improved clinical outcomes can be expected for male patients without obesity who are undergoing medial meniscectomy with minimal meniscal resection. Varus or valgus deformities, preexisting degenerative changes in the knee, and anterior cruciate ligament deficiency negatively impact outcomes following meniscectomy. Failure rates following meniscectomy are relatively low compared with meniscal repair and discoid saucerizations, although revision rates are increased in patients undergoing lateral meniscectomy. Meniscectomy increases the risk of developing knee osteoarthritis (OA), particularly in female patients with obesity who undergo large meniscal resection. Because of the risk of developing OA, there is a corresponding increase in the likelihood of total knee arthroplasty following meniscectomy.